2021
DOI: 10.1016/j.jmig.2020.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Radical Hysterectomy for Cervical Cancer: A Systematic Review and Meta-analysis

Abstract: Objective: To compare recurrence rate, progression-free survival (PFS), and overall survival for early-stage cervical cancer after minimally invasive (MIS) vs abdominal radical hysterectomy. Data Sources: MEDLINE, Embase, Cochrane Central Register of Controlled Trials, and Cochrane Library databases. Methods of Study Selection: We identified studies from 1990 to 2020 that included women with stage I or higher cervical cancer treated with primary radical hysterectomy and compared recurrence and/or PFS and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
1
16
1
Order By: Relevance
“…3,29 Also, more and more studies have challenged the perceived oncologic safety of minimally invasive surgery for early-stage cervical cancer. [30][31][32][33] After controlling for potential confounding prognostic factors, our study identified advanced age at diagnosis, high-grade tumor, and LVSI as the independent risk factors for worse long-term survival outcomes in patients with stage IA2 cervical cancer; this result is consistent with that of other studies. [34][35][36] However, our study found that a minimally invasive surgical approach was not associated with the deterioration of survival in stage IA2 cervical cancer.…”
supporting
confidence: 90%
“…3,29 Also, more and more studies have challenged the perceived oncologic safety of minimally invasive surgery for early-stage cervical cancer. [30][31][32][33] After controlling for potential confounding prognostic factors, our study identified advanced age at diagnosis, high-grade tumor, and LVSI as the independent risk factors for worse long-term survival outcomes in patients with stage IA2 cervical cancer; this result is consistent with that of other studies. [34][35][36] However, our study found that a minimally invasive surgical approach was not associated with the deterioration of survival in stage IA2 cervical cancer.…”
supporting
confidence: 90%
“…In 2018, the results from the Laparoscopic Approach to Cervical Cancer (LACC) trial, a randomized controlled trial, on surgery in early-stage cervical cancer showed that MIS had poorer survival outcomes compared to laparotomy 4 . Since then, a great number of regarding studies have been reported and most of them have supported that MIS had poor survival outcome in cervical cancer patients 5 - 7 . However, most of the evaluated patients who had MIS had laparoscopic radical hysterectomy (LRH), not robotic radical hysterectomy (RRH).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ramirez et al (4) reported a multicenter randomized controlled trial (RCT), namely, the LACC trial, which showed that MIS was associated with lower 4.5-year disease-free survival (DFS), progression-free survival (PFS), overall survival (OS), and disease-specific survival rates and a higher local recurrence rate than the laparotomic approach. Several multicenter retrospective studies from different countries have validated this finding (5)(6)(7)(8). Reasons beyond these results are unclear.…”
Section: Introductionmentioning
confidence: 77%